Positive electrode active substance for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2024221497
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-08-29
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2039-02-27
AI Technical Summary
【0011】 本開示の一態様によれば、Niの割合がLiを除く金属元素の総量に対して75モル%~95モル%の範囲であるリチウム遷移金属酸化物を含む正極活物質の熱安定性を高めることが可能となる。
Smart Images

Figure 2025031774000001 
Figure 2025031774000002 
Figure 2025031774000003
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for a non-aqueous electrolyte secondary battery and a technology of a non-aqueous electrolyte secondary battery.
Background Art
[0002] In recent years, as a secondary battery with high output and high energy density, a non-aqueous electrolyte secondary battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte, which performs charge and discharge by moving lithium ions or the like between the positive electrode and the negative electrode, has been widely used.
[0003] As the positive electrode active material used for the positive electrode of the non-aqueous electrolyte secondary battery, for example, the following are known.
[0004] For example, Patent Document 1 discloses a positive electrode active material composed of a composite oxide represented by the composition formula Li a Ni b Co c Mn d O2 (where 0.1 ≦ a ≦ 1.2, 0.40 ≦ b < 1.15, 0 < c < 0.60, 0 < d < 0.60, and 1.00 ≦ b + c + d ≦ 1.15, 0 < c + d ≦ 0.60), and the transition metal occupancy e of the Li layer is in the range of 0.006 ≦ e ≦ 0.150.
[0005] Also, for example, Patent Document 2 discloses [Li] 3a [Ni 1-x-y Co x Al y 3b [O2] 6c (However, the subscript in [ ] represents a site, and x and y satisfy the conditions of 0 < x ≦ 0.20 and 0 < y ≦ 0.15). In a hexagonal lithium nickel composite oxide having a layered structure, the site occupancy of metal ions other than lithium at the 3a site obtained from the Rietveld analysis of the X-ray diffraction pattern is 3% or less, and the average particle diameter of the primary particles is 0.1 μm or more, and the primary particles are aggregated to form secondary particles. A positive electrode active material is disclosed.
Prior Art Documents
Patent Documents
[0006] [Patent Document 1] JP 2000-133262 A [Patent Document 2] JP 2000-30693 A Summary of the Invention [Problem to be solved by the invention]
[0007] By the way, a positive electrode active material containing a lithium transition metal oxide in which the ratio of Ni is in the range of 75 mol% to 95 mol% relative to the total amount of metal elements excluding Li exhibits a high charge / discharge capacity, but has a problem of low thermal stability. If the thermal stability of the positive electrode is low, the self-heating start temperature of the battery will be low, and if the temperature inside the battery rises due to overcharging, short circuit, etc., further chemical reactions accompanied by heat generation (self-heating reactions) will proceed in the battery as the temperature rises, and there is a risk that the temperature of the battery will rise further.
[0008] Therefore, an object of the present disclosure is to improve the thermal stability of a positive electrode active material containing a lithium transition metal oxide in which the proportion of Ni is in the range of 75 mol % to 95 mol % relative to the total amount of metal elements excluding Li. [Means for solving the problem]
[0009] A positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure comprises a lithium transition metal oxide containing Ni, Mn, and optionally Co, and having a layered structure, wherein a ratio of Ni to a total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 75 mol % to 95 mol %, a ratio of Mn to a total amount of metal elements excluding Li in the lithium transition metal oxide is greater than a ratio of Co to a total amount of metal elements excluding Li in the lithium transition metal oxide, and the lithium transition metal oxide is characterized in that a half width n of a diffraction peak of a (208) plane in an X-ray diffraction pattern obtained by X-ray diffraction satisfies 0.30°≦n≦0.50°.
[0010] A nonaqueous electrolyte secondary battery according to one aspect of the present disclosure is characterized by including a positive electrode having the above-described positive electrode active material for nonaqueous electrolyte secondary batteries. Effect of the Invention
[0011] According to one embodiment of the present disclosure, it is possible to improve the thermal stability of a positive electrode active material containing a lithium transition metal oxide in which the proportion of Ni is in the range of 75 mol % to 95 mol % with respect to the total amount of metal elements excluding Li. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] A positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure comprises a lithium transition metal oxide containing Ni, Mn, and an optional element Co, and having a layered structure, wherein a ratio of Ni to a total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 75 mol % to 95 mol %, a ratio of Mn to a total amount of metal elements excluding Li in the lithium transition metal oxide is equal to or greater than a ratio of Co to a total amount of metal elements excluding Li in the lithium transition metal oxide, a ratio of Co to a total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 0 mol % to 2 mol %, a ratio of metal elements excluding Li present in the Li layer of the layered structure is in the range of 1 mol % to 2.5 mol % to a total amount of metal elements excluding Li in the lithium transition metal oxide, and the lithium transition metal oxide has a half width n of a diffraction peak of a (208) plane in an X-ray diffraction pattern obtained by X-ray diffraction, which is 0.30°≦n≦0.50°.
[0013] Generally, lithium transition metal oxides in which the proportion of Ni is in the range of 75 mol % to 95 mol % relative to the total amount of metal elements excluding Li have low thermal stability. This is believed to be because lithium transition metal oxides in which the proportion of Ni is 75 mol % or more have low structural stability.
[0014] However, according to one aspect of the present disclosure, it is presumed that the Mn contained in the lithium transition metal oxide suppresses the release of oxygen in the layered structure, and that the presence of a predetermined amount of metal elements other than Li in the Li layer of the layered structure suppresses the repulsion between O--O in the layered structure during charging, thereby stabilizing the layered structure. In addition, it is presumed that the reactivity of Ni is suppressed by setting the proportion of Ni to 95 mol% or less, so that the effect of the Mn and the effect of the metal elements other than Li present in a predetermined amount in the Li layer of the layered structure are sufficiently obtained, thereby stabilizing the layered structure. Furthermore, it is presumed that the effect of the Mn is sufficiently obtained and the layered structure is stabilized by limiting the amount of Co contained in the lithium transition metal oxide and making the content of Mn greater than the content of Co, thereby stabilizing the layered structure. In addition, the half-width of the diffraction peak of the (208) plane in the X-ray diffraction pattern by X-ray diffraction is an index showing the fluctuation of the arrangement between the Li layer and the transition metal layer in the layered structure, and when it is within the above-mentioned predetermined range as in one embodiment of the present disclosure, it is considered that this leads to the stabilization of the layered structure because a moderate fluctuation occurs in the arrangement between the Li layer and the transition metal layer in the layered structure. Thus, each of the above-mentioned configurations according to one embodiment of the present disclosure contributes to the stabilization of the layered structure of the lithium transition metal oxide, and the effect of increasing the thermal stability is brought about only by the combination of the above-mentioned configurations.
[0015] Hereinafter, an example of a nonaqueous electrolyte secondary battery using the positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure will be described.
[0016] The nonaqueous electrolyte secondary battery, which is an example of the embodiment, includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. It is preferable to provide a separator between the positive electrode and the negative electrode. Specifically, the battery has a structure in which a wound electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, and a nonaqueous electrolyte are housed in an outer casing. The electrode body is not limited to a wound electrode body, and other types of electrode bodies may be applied, such as a laminated electrode body in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween. In addition, the type of the nonaqueous electrolyte secondary battery is not particularly limited, and examples thereof include a cylindrical type, a square type, a coin type, a button type, and a laminate type.
[0017] The positive electrode, negative electrode, nonaqueous electrolyte, and separator used in the nonaqueous electrolyte secondary battery, which is one example of the embodiment, will be described in detail below.
[0018] <Positive electrode> The positive electrode is composed of a positive electrode current collector such as a metal foil and a positive electrode active material layer formed on the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having the metal disposed on the surface layer. The positive electrode active material layer includes, for example, a positive electrode active material, a binder, a conductive material, etc.
[0019] The positive electrode is obtained, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, etc., onto a positive electrode current collector, drying the slurry, thereby forming a positive electrode active material layer on the positive electrode current collector, and then rolling the positive electrode active material layer.
[0020] The positive electrode active material includes a lithium transition metal oxide having a layered structure and containing Ni, Mn, and optionally Co. Hereinafter, the lithium transition metal oxide having a layered structure and containing Ni, Mn, and optionally Co is referred to as the "lithium transition metal oxide of the present embodiment."
[0021] Examples of the layered structure of the lithium transition metal oxide of this embodiment include a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, etc. Among these, a layered structure belonging to the space group R-3m is preferred in terms of high capacity, stability of the layered structure, etc.
[0022] The ratio of Ni to the total amount of metal elements other than Li in the lithium transition metal oxide of this embodiment is in the range of 75 mol% to 95 mol%, preferably 85 mol% to 95 mol%, from the viewpoints of increasing the capacity of the battery and improving the thermal stability. If the ratio of Ni exceeds 95 mol%, the reactivity of Ni increases, and the stability of the layered structure decreases, causing a decrease in thermal stability. If the ratio of Ni is less than 75 mol%, it becomes difficult to increase the capacity of the battery in the first place.
[0023] The ratio of Mn to the total amount of metal elements excluding Li in the lithium transition metal oxide of this embodiment may be equal to or greater than the ratio of Co to the total amount of metal elements excluding Li in the lithium transition metal oxide of this embodiment in terms of increasing thermal stability, but is preferably in the range of 1 mol% to 10 mol%, and more preferably in the range of 2 mol% to 8 mol%. If the ratio of Co is greater than the ratio of Mn, oxygen release in the layered structure is not suppressed, and the stability of the layered structure is reduced, causing a decrease in thermal stability.
[0024] In terms of increasing thermal stability, etc., the ratio of Co to the total amount of metal elements excluding Li in the lithium transition metal oxide of this embodiment is in the range of 0 mol % to 2 mol %, and preferably in the range of 0.5 to 2. If the ratio of Co exceeds 2 mol %, for example, the above-mentioned effect of Mn is reduced, and the stability of the layered structure is reduced, causing a decrease in thermal stability.
[0025] The lithium transition metal oxide of the present embodiment may contain metal elements other than Li, Ni, Mn, and Co, and examples thereof include at least one metal element selected from Al, Fe, Mg, Si, Ti, Cr, Cu, Sn, Zr, Nb, Mo, Ta, W, Na, K, Ba, Sr, Bi, Be, Zn, Ca, and B. Among these, at least one metal element selected from Al, Fe, Nb, Si, Mo, and Ti is preferred from the viewpoint of suppressing deterioration of charge-discharge cycle characteristics, and among these, Al is more preferred. The other metal element may be, for example, uniformly dispersed in the layered structure of the lithium transition metal oxide of the present embodiment, or may be present in a part of the layered structure. In addition, in the production stage of the lithium transition metal oxide of the present embodiment, a part of the other metal element contained in the layered structure may precipitate on the particle surface of the lithium transition metal oxide of the present embodiment, and this precipitated metal element is also a metal element constituting the lithium transition metal oxide of the present embodiment.
[0026] The content of elements constituting the lithium transition metal oxide of this embodiment can be measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0027] In the lithium transition metal oxide of this embodiment, metal elements other than Li are present in the Li layer of the layered structure. The ratio of metal elements other than Li present in the Li layer of the layered structure is 1 mol% to 2.5 mol%, preferably 1 mol% to 2 mol%, based on the total amount of metal elements other than Li in the lithium transition metal oxide, in order to increase the self-heating starting temperature. If the ratio of metal elements other than Li present in the Li layer of the layered structure is outside the above range, the stability of the layered structure is reduced, causing a reduction in thermal stability. The metal elements other than Li present in the Li layer of the layered structure are mainly Ni, based on the ratio of elements constituting the lithium transition metal oxide of this embodiment, but other metal elements may also be present.
[0028] The proportion of metal elements other than Li present in the Li layer of the layered structure can be obtained from the results of Rietveld analysis of the X-ray diffraction pattern obtained by X-ray diffraction measurement of the lithium transition metal oxide of this embodiment.
[0029] The X-ray diffraction pattern is obtained by a powder X-ray diffraction method using a powder X-ray diffractometer (manufactured by Rigaku Corporation, product name "RINT-TTR", radiation source Cu-Kα) under the following conditions. Measurement range: 15-120° Scan speed: 4° / min Analysis range: 30-120° Background; B-spline Profile function; split pseudo-Voigt function Constraint condition; Li(3a) + Ni(3a)=1 Ni(3a) + Ni(3b) = y ICSD No.;98-009-4814
[0030] In addition, the Rietveld analysis software PDXL2 (Rigaku Corporation) is used for the Rietveld analysis of the X-ray diffraction patterns.
[0031] In the lithium transition metal oxide of this embodiment, the half-width n of the diffraction peak of the (208) plane in the X-ray diffraction pattern by the above X-ray diffraction is 0.30°≦n≦0.50°, and preferably 0.30°≦n≦0.45°, in terms of increasing thermal stability, etc. If the half-width n of the diffraction peak of the (208) plane is outside the above range, the fluctuation in the arrangement between the Li layer and the transition metal layer in the layered structure becomes too small or too large, reducing the stability of the layered structure and causing a decrease in thermal stability.
[0032] In the lithium transition metal oxide of this embodiment, the lattice constant a indicating the a-axis length of the crystal structure obtained from the result of the X-ray diffraction pattern by the X-ray diffraction is preferably in the range of 2.867 Å≦a≦2.877 Å, and the lattice constant c indicating the c-axis length is preferably in the range of 14.18 Å≦c≦14.21 Å. When the lattice constant a is smaller than 2.867 Å, the atomic distance in the crystal structure may be narrower and more unstable than when the above range is satisfied, and the thermal stability may be reduced. When the lattice constant a is larger than 2.877 Å, the atomic distance in the crystal structure may be wider and more unstable than when the above range is satisfied, and the thermal stability may be reduced. When the lattice constant c is smaller than 14.18 Å, the atomic distance in the crystal structure may be narrower and more unstable than when the above range is satisfied, and the thermal stability may be reduced. Furthermore, if the lattice constant c is greater than 14.21 Å, the interatomic distance in the crystal structure becomes large, resulting in an unstable structure, which may cause a decrease in thermal stability compared to when the above range is satisfied.
[0033] The lithium transition metal oxide of this embodiment preferably has a crystallite size s of 400 Å≦s≦650 Å, calculated from the half-width of the diffraction peak of the (104) plane in the X-ray diffraction pattern by the Scherrer equation. If the crystallite size s of the lithium transition metal oxide of this embodiment is outside the above range, the stability of the layered structure may decrease, causing a decrease in thermal stability. The Scherrer equation is expressed by the following formula:
[0034] s=Kλ / Bcosθ In the formula, s is the crystallite size, λ is the wavelength of the X-ray, B is the half-width of the diffraction peak of the (104) plane, θ is the diffraction angle (rad), and K is the Scherrer constant. In this embodiment, K is set to 0.9.
[0035] The content of the lithium transition metal oxide in this embodiment is preferably 90 mass% or more, and more preferably 99 mass% or more, relative to the total mass of the positive electrode active material, for example, in order to effectively increase the thermal stability of the positive electrode active material.
[0036] The positive electrode active material of the present embodiment may contain other lithium transition metal oxides in addition to the lithium transition metal oxide of the present embodiment, such as lithium transition metal oxides having a Ni content of 0 mol % to less than 75 mol %.
[0037] An example of a method for producing the lithium transition metal oxide of this embodiment will be described.
[0038] The method for producing the lithium transition metal oxide of this embodiment includes, for example, a first step of obtaining a composite oxide containing Ni, Mn, and an arbitrary metal element, a second step of mixing the composite oxide obtained in the first step with a Li compound, and a third step of firing the mixture. In the lithium transition metal oxide of this embodiment finally obtained, the ratio of metal elements other than Li present in the Li layer of the layered structure, the half-width n of the diffraction peak of the (208) plane, the lattice constant a, the lattice constant c, the crystallite size s, and other parameters are adjusted by controlling the mixing ratio of the raw materials in the second step and the firing conditions in the third step.
[0039] In the first step, for example, while stirring a solution of a metal salt containing Ni, Mn, and an arbitrary metal element (Co, Al, etc.), an alkaline solution such as sodium hydroxide is dropped to adjust the pH to the alkaline side (for example, 8.5 to 14.0), thereby precipitating (co-precipitating) a composite hydroxide containing Ni, Mn, and the arbitrary metal element, and the composite hydroxide is fired to obtain a composite oxide containing Ni, Mn, and the arbitrary metal element. The blending ratio of Ni and the arbitrary metal element may be appropriately determined so that the ratio of Ni, Mn, etc. falls within the above range. The firing temperature is not particularly limited, but is, for example, in the range of 500°C to 600°C.
[0040] In the second step, the composite oxide obtained in the first step is mixed with a Li compound to obtain a mixture. The mixing ratio of the composite oxide obtained in the first step and the Li compound is set such that the molar ratio of metal elements other than Li:Li is in the range of 1:0.98 to 1:1.08 in order to adjust each of the parameters within the ranges specified above. In the second step, when the composite oxide obtained in the first step is mixed with the Li compound, other metal raw materials may be added as necessary. The other metal raw materials are oxides containing metal elements other than Li and metal elements constituting the composite oxide obtained in the first step.
[0041] In the third step, the mixture obtained in the second step is fired at a predetermined temperature and time to obtain the lithium transition metal oxide according to the present embodiment. The firing of the mixture in the third step is performed in the following two-stage firing in order to adjust each of the parameters to the above-specified ranges. The firing conditions in the first stage are, for example, firing at a temperature rise rate in the range of 5.5°C / min to 1.5°C / min to a temperature range of 450°C to 650°C, and the temperature retention time is 0 to 5 hours. The firing conditions in the second stage are, for example, firing at a temperature rise rate in the range of 3.5°C / min to 0.1°C / min to a temperature range of the first stage to 800°C, and the temperature retention time is 1 to 10 hours. When firing the mixture, in order to adjust each of the parameters to the above-specified ranges, the firing is performed in an oxygen stream with an oxygen concentration of 60% or more, and the flow rate of the oxygen stream is set to 10 cm / min. 3 The flow rate should be in the range of 0.2mL / min to 4mL / min per kg of mixture and 0.3L / min or more per kg of mixture.
[0042] Other materials contained in the positive electrode active material layer will be described below.
[0043] Examples of the conductive material contained in the positive electrode active material layer include carbon powders such as carbon black, acetylene black, ketjen black, and graphite. These may be used alone or in combination of two or more.
[0044] Examples of the binder contained in the positive electrode active material layer include fluorine-based polymers, rubber-based polymers, etc. Examples of the fluorine-based polymers include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), or modified versions of these, and examples of the rubber-based polymers include ethylene-propylene-isoprene copolymers, ethylene-propylene-butadiene copolymers, etc. These may be used alone or in combination of two or more.
[0045] <Negative electrode> The negative electrode includes a negative electrode current collector such as a metal foil and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode current collector may be a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having the metal disposed on the surface layer. The negative electrode active material layer includes, for example, a negative electrode active material, a binder, a thickener, and the like.
[0046] The negative electrode is obtained, for example, by applying a negative electrode mixture slurry containing a negative electrode active material, a thickener, and a binder onto a negative electrode current collector, followed by drying to form a negative electrode active material layer on the negative electrode current collector, and then rolling the negative electrode active material layer.
[0047] The negative electrode active material contained in the negative electrode active material layer is not particularly limited as long as it is a material capable of absorbing and releasing lithium ions, and examples thereof include carbon materials, metals capable of forming an alloy with lithium, or alloy compounds containing such metals. Examples of carbon materials include graphites such as natural graphite, non-graphitizable carbon, and artificial graphite, and cokes. Examples of alloy compounds include those containing at least one metal capable of forming an alloy with lithium. Examples of elements capable of forming an alloy with lithium include silicon and tin, and silicon oxide and tin oxide, which are formed by combining these with oxygen, can also be used. In addition, a mixture of the carbon material and a compound of silicon or tin can be used. In addition to the above, a material having a charge / discharge potential with respect to metallic lithium, such as lithium titanate, higher than that of the carbon material can also be used.
[0048] The binder contained in the negative electrode active material layer may be, for example, a fluoropolymer, a rubber-based polymer, or the like, as in the case of the positive electrode, but styrene-butadiene copolymer (SBR) or a modified product thereof may also be used. The binder contained in the negative electrode active material layer may be, for example, a fluororesin, PAN, a polyimide resin, an acrylic resin, a polyolefin resin, or the like, as in the case of the positive electrode. When preparing the negative electrode mixture slurry using an aqueous solvent, it is preferable to use styrene-butadiene rubber (SBR), CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof (PAA-Na, PAA-K, or the like, or a partially neutralized salt), polyvinyl alcohol (PVA), or the like.
[0049] Examples of the thickener contained in the negative electrode active material layer include carboxymethyl cellulose (CMC), polyethylene oxide (PEO), etc. These may be used alone or in combination of two or more.
[0050] <Non-aqueous electrolyte> The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (non-aqueous electrolyte solution), and may be a solid electrolyte using a gel-like polymer or the like. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, or a mixed solvent of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine.
[0051] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, and γ-butyrolactone.
[0052] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, and the like. and chain ethers such as ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0053] As the halogen-substituted compound, it is preferable to use a fluorinated cyclic carbonate such as fluoroethylene carbonate (FEC), a fluorinated chain carbonate, a fluorinated chain carboxylate such as methyl fluoropropionate (FMP), or the like.
[0054] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 、LiCl、LiBr、LiI、lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), imide salts such as LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more}, etc. Among these, from the viewpoints of ionic conductivity, electrochemical stability, etc., it is preferable to use LiPF6. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the non-aqueous solvent.
[0055] <Separator> The separator may be, for example, a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator may be made of an olefin resin such as polyethylene or polypropylene, or cellulose. The separator may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin, or a separator having an aramid resin or the like applied to its surface. A filler layer containing an inorganic filler may be formed at the interface between the separator and at least one of the positive electrode and the negative electrode. Examples of the inorganic filler include oxides containing at least one of titanium (Ti), aluminum (Al), silicon (Si), and magnesium (Mg), phosphate compounds, and those whose surfaces are treated with hydroxides or the like. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode, the negative electrode, or the separator. EXAMPLES
[0056] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples.
[0057] <Example 1> [Preparation of positive electrode active material] Composite oxide containing Ni, Mn, Co and Al (Ni 0.90 Mn 0.04 Co 0.02 Al 0.04 O2) and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, Co, and Al to Li was 1:1.03. The flow rate was 10 cm 3The mixture was fired in an oxygen stream with an oxygen concentration of 95% at a temperature rise rate of 3.5°C / min up to 650°C, and then fired at a temperature rise rate of 0.5°C / min from 650°C to 730°C. The fired product was washed with water to obtain a lithium transition metal oxide. The proportions of Ni, Mn, Co, and Al in the lithium transition metal oxide obtained above were measured, and the results were Ni 90 mol%, Mn 4 mol%, Co 2 mol%, and Al 4 mol%.
[0058] In addition, the lithium transition metal oxide of Example 1 was subjected to powder X-ray diffraction measurement under the above-mentioned conditions to obtain an X-ray diffraction pattern. As a result, a diffraction line showing a layered structure was confirmed, and the ratio of metal elements other than Li present in the Li layer was 1.7 mol%, the half-width of the diffraction peak of the (208) plane was 0.43°, the lattice constant a was 2.873 Å, the lattice constant c was 14.20 Å, and the crystallite size s was 548 Å. This was used as the positive electrode active material of Example 1.
[0059] <Comparative Example 1-1> Composite oxide containing Ni, Mn, Co and Al (Ni 0.93 Co 0.02 Al 0.05 O2), Ti(OH)4, and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, Co, Al, and Ti to Li was 1:1.05. The flow rate was 10 cm 3 A lithium transition metal oxide was produced in the same manner as in Example 1, except that the flow rates were 0.1 mL / min per kg of transition metal oxide and 0.25 L / min per kg of transition metal oxide. The proportions of Ni, Co, Al, and Ti in the obtained lithium transition metal oxide were measured, and the results were as follows: Ni proportion was 90 mol %, Co proportion was 2 mol %, Al proportion was 5 mol %, and Ti proportion was 3 mol %.
[0060] In addition, the lithium transition metal oxide of Comparative Example 1-1 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.4 mol %, and the half-width of the diffraction peak of the (208) plane was 0.37°. This was used as the positive electrode active material of Comparative Example 1-1.
[0061] <Comparative Example 1-2> A lithium transition metal oxide was produced in the same manner as in Example 1, except that the molar ratio of the total amount of Ni, Mn, Co and Al to Li was 1:0.97. The proportions of Ni, Mn, Co and Al in the lithium transition metal oxide obtained above were measured, and the results were that the proportion of Ni was 90 mol %, the proportion of Mn was 4 mol %, the proportion of Co was 2 mol %, and the proportion of Al was 4 mol %.
[0062] In addition, the lithium transition metal oxide of Comparative Example 1-2 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 3 mol %, and the half-width of the diffraction peak of the (208) plane was 0.48°. This was used as the positive electrode active material of Comparative Example 1-2.
[0063] <Comparative Example 1-3> A lithium transition metal oxide was produced in the same manner as in Example 1, except that Ni, Mn, Co and Al were mixed so that the molar ratio of the total amount of Ni, Mn, Co and Al to Li was 1:1.1. The proportions of Ni, Mn, Co and Al in the lithium transition metal oxide obtained above were measured, and the results were that the proportion of Ni was 90 mol %, the proportion of Mn was 4 mol %, the proportion of Co was 2 mol % and the proportion of Al was 4 mol %.
[0064] In addition, the lithium transition metal oxide of Comparative Example 1-3 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 0.5 mol %, and the half-width of the diffraction peak of the (208) plane was 0.31°. This was used as the positive electrode active material of Comparative Example 1-3.
[0065] <Comparative Example 1-4> Composite oxide containing Ni, Mn, Co and Al (Ni 0.92 Co 0.02 Al 0.05 A lithium transition metal oxide was produced in the same manner as in Example 1, except that Ni, Mn, Co, Al, and Nb were mixed with Nb2O5 and LiOH in such a way that the molar ratio of the total amount of Ni, Mn, Co, Al, and Nb to Li was 1:1.1, and the mixture was fired at a heating rate of 1°C / min up to 650°C, and then fired at a heating rate of 0.05°C / min from 650°C to 730°C. The proportions of Ni, Mn, Co, Al, and Nb in the lithium transition metal oxide obtained above were measured, and the results were as follows: Ni was 90 mol%, Mn was 4 mol%, Co was 2 mol%, Al was 2 mol%, and Nb was 2 mol%.
[0066] In addition, the lithium transition metal oxide of Comparative Example 1-4 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 3 mol %, and the half-width of the diffraction peak of the (208) plane was 0.23°. This was designated as the positive electrode active material of Comparative Example 1-4.
[0067] <Comparative Example 1-5> A lithium transition metal oxide was produced in the same manner as in Example 1, except that the molar ratio of the total amount of Ni, Mn, Co and Al to Li was changed to 1:1.1, and the maximum firing temperature was changed to 680° C. The proportions of Ni, Mn, Co and Al in the lithium transition metal oxide obtained above were measured, and the results were that the Ni proportion was 90 mol %, the Mn proportion was 4 mol %, the Co proportion was 2 mol %, and the Al proportion was 4 mol %.
[0068] In addition, the lithium transition metal oxide of Comparative Example 1-5 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 0.5 mol %, and the half-width of the diffraction peak of the (208) plane was 0.64°. This was designated as the positive electrode active material of Comparative Example 1-5.
[0069] [Preparation of positive electrode] The positive electrode active material of Example 1 was mixed in a ratio of 95 parts by mass, 3 parts by mass of acetylene black as a conductive material, and 2 parts by mass of polyvinylidene fluoride as a binder. The mixture was kneaded using a kneader (TK Hibismix, manufactured by Primix Corporation) to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to an aluminum foil having a thickness of 15 μm, and the coating was dried to form a positive electrode active material layer on the aluminum foil. This was the positive electrode of Example 1. Positive electrodes were also prepared in the same manner for Comparative Examples 1-1 to 1-5.
[0070] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.
[0071] [Preparation of test cell] The positive electrode of Example 1 and the negative electrode using graphite as the negative electrode active material were stacked so as to face each other with a separator interposed therebetween, and the stack was wound to prepare an electrode assembly. Next, the electrode assembly and the non-aqueous electrolyte were inserted into an aluminum exterior body to prepare a test cell. Test cells of Comparative Examples 1-1 to 1-5 were also prepared in the same manner.
[0072] [Runaway reaction measurement test] The self-heating starting temperature of the battery was measured under the following conditions using an accelerated rate calorimeter (ARC, manufactured by Thermal Hazard Technology). Measurement start temperature: 100℃ Holding temperature: 20min Heat generation detection temperature: 0.02℃ / min Temperature rise: 5℃ Battery voltage: 4.2V state of charge If no rise in temperature above the heat generation detection temperature was detected within 20 minutes from the start of measurement, the temperature was raised to the next step and measurement was performed again. If a rise in temperature above the heat generation detection temperature was detected, it was determined that self-heating had begun, and the temperature at that point was recorded as the self-heating start temperature.
[0073] Table 1 summarizes the results of the self-heating onset temperature of the batteries of Example 1 and Comparative Examples 1-1 to 1-5. In Table 1, the self-heating onset temperature of Comparative Example 1-1 is used as a reference, and the difference between the self-heating onset temperature of Example 1 and the other Comparative Examples is calculated and shown as the amount of change in self-heating onset temperature. Therefore, a positive value indicates that the self-heating onset temperature is increased and the thermal stability of the positive electrode active material is improved.
[0074] [Table 1]
[0075] As can be seen from the results in Table 1, only in Example 1, the self-heating initiation temperature was increased, and the thermal stability of the positive electrode active material was improved.
[0076] <Example 2> [Preparation of positive electrode active material] Composite oxide containing Ni, Mn and Co (Ni 0.94 Mn 0.04 Co 0.02 O2) and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, and Co to Li was 1:1.03. The flow rate was 10 cm 3 The mixture was fired in an oxygen stream with an oxygen concentration of 95%, at a temperature rise rate of 3.5°C / min up to 650°C, and then at a temperature rise rate of 0.5°C / min from 650°C to 700°C. The fired product was washed with water to obtain a lithium transition metal oxide. The proportions of Ni, Mn, and Co in the lithium transition metal oxide obtained above were measured, and the results were that the Ni proportion was 94 mol%, the Mn proportion was 4 mol%, and the Co proportion was 2 mol%.
[0077] In addition, the lithium transition metal oxide of Example 2 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1, and as a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 2.1 mol %, the half-width of the diffraction peak of the (208) plane was 0.44°, the lattice constant a was 2.875 Å, the lattice constant c was 14.21 Å, and the crystallite size s was 607 Å. This was used as the positive electrode active material of Example 2.
[0078] <Comparative Example 2-1> The composite oxide containing Ni, Mn, and Co is called the composite oxide containing Ni, Mn, and Al (Ni 0.94 Mn 0.02 Co 0.03 Al 0.01 A lithium transition metal oxide was produced in the same manner as in Example 2, except that the content of Ni in the lithium transition metal oxide was changed to O2. The proportions of Ni, Mn, Co, and Al in the lithium transition metal oxide obtained above were measured, and the results were that the proportion of Ni was 94 mol %, the proportion of Mn was 2 mol %, the proportion of Co was 3 mol %, and the proportion of Al was 1 mol %.
[0079] In addition, the lithium transition metal oxide of Comparative Example 2-1 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.4 mol %, and the half-width of the diffraction peak of the (208) plane was 0.32°. This was used as the positive electrode active material of Comparative Example 2-1.
[0080] <Comparative Example 2-2> The composite oxide containing Ni, Mn and Co is called the composite oxide containing Ni, Mn and Co (Ni 0.94 Mn 0.03 Co 0.03 A lithium transition metal oxide was produced in the same manner as in Example 2, except that the amount of Ni, Mn, and Co in the lithium transition metal oxide was changed to O2. The proportions of Ni, Mn, and Co in the lithium transition metal oxide obtained above were measured, and the proportion of Ni was 94 mol %, the proportion of Mn was 3 mol %, and the proportion of Co was 3 mol %.
[0081] In addition, the lithium transition metal oxide of Comparative Example 2-2 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.9 mol %, and the half-width of the diffraction peak of the (208) plane was 0.49°. This was used as the positive electrode active material of Comparative Example 2-2.
[0082] <Comparative Example 2-3> The composite oxide containing Ni, Mn, and Co is called the composite oxide containing Ni, Mn, and Al (Ni 0.94 Mn 0.01 Co 0.02 Al 0.03 A lithium transition metal oxide was produced in the same manner as in Example 2, except that the content of Ni in the lithium transition metal oxide was changed to O2. The proportions of Ni, Mn, Co, and Al in the lithium transition metal oxide obtained above were measured, and the results were that the proportion of Ni was 94 mol%, the proportion of Mn was 1 mol%, the proportion of Co was 2 mol%, and the proportion of Al was 3 mol%.
[0083] In addition, the lithium transition metal oxide of Comparative Example 2-3 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.6 mol %, and the half-width of the diffraction peak of the (208) plane was 0.32°. This was used as the positive electrode active material of Comparative Example 2-3.
[0084] <Comparative Example 2-4> A composite oxide containing Ni, Mn, and Co was used as a composite oxide containing Ni, Co, and Al (Ni 0.94 Co 0.015 Al 0.045 A lithium transition metal oxide was produced in the same manner as in Example 2, except that O2 was changed to O. The proportions of Ni, Co, and Al in the lithium transition metal oxide obtained above were measured, and the results were that the proportion of Ni was 94 mol %, the proportion of Co was 1.5 mol %, and the proportion of Al was 4.5 mol %.
[0085] In addition, the lithium transition metal oxide of Comparative Example 2-4 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1. As a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 1.1 mol %, and the half-width of the diffraction peak of the (208) plane was 0.4°. This was used as the positive electrode active material of Comparative Example 2-4.
[0086] Test cells were prepared in the same manner as in Example 1 using the positive electrode active materials of Example 2 and Comparative Examples 2-1 to 2-4, and the self-heating starting temperatures of the batteries were measured under the same conditions as above.
[0087] Table 2 summarizes the results of the self-heating onset temperature of Example 2 and Comparative Examples 2-1 to 2-4. In Table 2, the self-heating onset temperature of Comparative Example 2-4 is used as a reference, and the difference between the self-heating onset temperature of Example 2 and the other Comparative Examples is calculated and shown as the amount of change in self-heating onset temperature. Therefore, a positive value indicates that the self-heating onset temperature is increased and the thermal stability of the positive electrode active material is improved.
[0088] [Table 2]
[0089] As can be seen from the results in Table 2, only in Example 2, the self-heating onset temperature was increased, and the thermal stability of the positive electrode active material was improved.
[0090] <Reference example 3-1> Composite oxide containing Ni, Mn, Co and Al (Ni 0.77 Mn 0.16 Co 0.02 Al 0.05 O2), Ti(OH)4, and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, Co, Al, and Ti to Li was 1:1.05. The flow rate was 10 cm 3The mixture was fired in an oxygen stream with an oxygen concentration of 95% at a temperature rise rate of 3.5°C / min up to 650°C, and then fired at a temperature rise rate of 0.5°C / min from 650°C to 780°C. The fired product was washed with water to obtain a lithium transition metal oxide. The proportions of Ni, Mn, and Co in the lithium transition metal oxide obtained above were measured, and the results were Ni 73 mol%, Mn 15 mol%, Co 2 mol%, Al 5 mol, and Ti 5 mol%.
[0091] In addition, the lithium transition metal oxide of Reference Example 3-1 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1, and diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 2.4 mol%, and the half-width of the diffraction peak of the (208) plane was 0.46°. This was used as the positive electrode active material of Reference Example 3-1. Using the positive electrode active material of Reference Example 3-1, a test cell was prepared in the same manner as in Example 1, and the self-heating start temperature of the battery was measured under the same conditions as above. In addition, a test cell was prepared using a lithium transition metal oxide that did not contain Mn and had a Ni ratio of 73 mol%, a Co ratio of 15 mol%, an Al ratio of 7 mol%, and a Ti ratio of 5 mol% as the positive electrode active material, and the self-heating start temperature (reference value) was measured under the same conditions as above to determine the self-heating start temperature change amount of Reference Example 3-1. The results are shown in Table 3.
[0092] <Example 3-2> Composite oxide containing Ni, Mn, Co and Al (Ni 0.82 Mn 0.11 Co 0.02 Al 0.05 A lithium transition metal oxide was produced in the same manner as in Reference Example 3-1, except that O2), Fe2O3, and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, Co, Al, and Fe to Li was 1:1.05. The proportions of Ni, Mn, Co, Al, and Fe in the lithium transition metal oxide obtained above were measured, and the results were as follows: Ni proportion was 77 mol %, Mn proportion was 10 mol %, Co proportion was 2 mol %, Al proportion was 5 mol %, and Fe proportion was 6 mol %.
[0093] In addition, the lithium transition metal oxide of Example 3-2 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1, and as a result, diffraction lines indicating a layered structure were confirmed, the ratio of metal elements other than Li present in the Li layer was 2.5 mol%, and the half-width of the diffraction peak of the (208) plane was 0.49°. This was used as the positive electrode active material of Example 3-2. Using the positive electrode active material of Example 3-2, a test cell was prepared in the same manner as in Example 1, and the self-heating start temperature was measured under the same conditions as above. In addition, a test cell was prepared using a lithium transition metal oxide that did not contain Mn and had a Ni ratio of 77 mol%, a Co ratio of 10 mol%, an Al ratio of 7 mol%, and an Fe ratio of 6 mol% as the positive electrode active material, and the self-heating start temperature (reference value) was measured under the same conditions as above to determine the self-heating start temperature change amount of Example 3-2. The results are shown in Table 3.
[0094] <Example 3-3> Composite oxide containing Ni, Mn, Co and Al (Ni 0.88 Mn 0.05 Co 0.02 Al 0.05 A lithium transition metal oxide was produced in the same manner as in Reference Example 3-1, except that 1,2-dihydro-1,2-trimethylaniline (O2), Fe2O3, and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, Co, Al, and Fe to Li was 1:1.05, and the maximum firing temperature was changed to 750° C. The proportions of Ni, Mn, Co, Al, and Fe in the lithium transition metal oxide obtained above were measured, and the results were as follows: Ni proportion 85 mol %, Mn proportion 5 mol %, Co proportion 2 mol %, Al proportion 5 mol %, and Fe proportion 3 mol %.
[0095] In addition, the lithium transition metal oxide of Example 3-3 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1, and diffraction lines indicating a layered structure were confirmed. The ratio of metal elements other than Li present in the Li layer was 1.7 mol%, the half-width of the diffraction peak of the (208) plane was 0.45°, the lattice constant a was 2.870 Å, the lattice constant c was 14.19 Å, and the crystallite size s was 454 Å. This was used as the positive electrode active material of Example 3-3. Using the positive electrode active material of Example 3-3, a test cell was prepared in the same manner as in Example 1, and the self-heating start temperature was measured under the same conditions as above. In addition, a test cell was prepared using a lithium transition metal oxide as the positive electrode active material, which was free of Mn, had a Ni ratio of 85 mol%, a Co ratio of 12 mol%, an Al ratio of 3 mol%, a ratio of metal elements other than Li present in the Li layer of 1.0 mol%, and a half-width of the diffraction peak of the (208) plane of 0.41°, and the self-heating onset temperature (reference value) was measured under the same conditions as above to determine the self-heating onset temperature change in Example 3-3. The results are shown in Table 3.
[0096] <Example 3-4> Composite oxide containing Ni, Mn, Co and Al (Ni 0.89 Mn 0.06 Co 0.02 Al 0.03 A lithium transition metal oxide was produced in the same manner as in Reference Example 3-1, except that Ni, Mn, Co, Al, Nb, and LiOH were mixed with Nb2O5 and LiOH so that the molar ratio of the total amount of Ni, Mn, Co, Al, and Nb to Li was 1:1.05, and the maximum firing temperature was changed to 750° C. The proportions of Ni, Mn, Co, Al, and Nb in the lithium transition metal oxide obtained above were measured, and the results were that the Ni proportion was 88.5 mol %, the Mn proportion was 6 mol %, the Co proportion was 2 mol %, the Al proportion was 3 mol %, and the Nb proportion was 0.5 mol %.
[0097] In addition, the lithium transition metal oxide of Example 3-4 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1, and diffraction lines indicating a layered structure were confirmed. The ratio of metal elements other than Li present in the Li layer was 2.1 mol%, the half-width of the diffraction peak of the (208) plane was 0.39°, the lattice constant a was 2.873 Å, the lattice constant c was 14.21 Å, and the crystallite size s was 521 Å. This was used as the positive electrode active material of Example 3-4. Using the positive electrode active material of Example 3-4, a test cell was prepared in the same manner as in Example 1, and the self-heating start temperature was measured under the same conditions as above. In addition, a test cell was prepared using a lithium transition metal oxide that did not contain Mn and had a Ni ratio of 88.5 mol%, a Co ratio of 8 mol%, an Al ratio of 3 mol%, and an Nb ratio of 0.5 mol% as the positive electrode active material, and the self-heating start temperature (reference value) was measured under the same conditions as above to obtain the self-heating start temperature change amount of Example 3-4. The results are shown in Table 3.
[0098] <Example 3-5> Composite oxide containing Ni, Mn, Co and Al (Ni 0.9 Mn 0.04 Co 0.02 Al 0.04 A lithium transition metal oxide was produced in the same manner as in Reference Example 3-1, except that O2) and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, Co, and Al to Li was 1:1.05, and the maximum firing temperature was changed to 730° C. The proportions of Ni, Mn, Co, and Al in the lithium transition metal oxide obtained above were measured, and the results were that the proportion of Ni was 90 mol %, the proportion of Mn was 4 mol %, the proportion of Co was 2 mol %, and the proportion of Al was 4 mol %.
[0099] In addition, the lithium transition metal oxide of Example 3-5 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1, and diffraction lines indicating a layered structure were confirmed. The ratio of metal elements other than Li present in the Li layer was 1.7 mol%, the half-width of the diffraction peak of the (208) plane was 0.43°, the lattice constant a was 2.873 Å, the lattice constant c was 14.20 Å, and the crystallite size s was 548 Å. This was used as the positive electrode active material of Example 3-5. Using the positive electrode active material of Example 3-5, a test cell was prepared in the same manner as in Example 1, and the self-heating start temperature was measured under the same conditions as above. In addition, a test cell was prepared using a lithium transition metal oxide as the positive electrode active material, which was free of Mn, had a Ni ratio of 90 mol%, a Co ratio of 6 mol%, an Al ratio of 4 mol%, a ratio of metal elements other than Li present in the Li layer of 1.2 mol%, and a half-width of the diffraction peak of the (208) plane of 0.42°, and the self-heating onset temperature (reference value) was measured under the same conditions as above to determine the self-heating onset temperature change in Examples 3-5. The results are shown in Table 3.
[0100] <Example 3-6> Composite oxide containing Ni, Mn, Co and Al (Ni 0.92 Mn 0.015 Co 0.015 Al 0.04 A lithium transition metal oxide was produced in the same manner as in Reference Example 3-1, except that SiO2), SiO, Fe2O3, and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, Co, Al, Si, and Fe to Li was 1:1.05, and the maximum firing temperature was changed to 700° C. The proportions of Ni, Mn, Co, Al, Si, and Fe in the lithium transition metal oxide obtained above were measured, and the results were that the Ni proportion was 90.5 mol %, the Mn proportion was 1.5 mol %, the Co proportion was 1.5 mol %, the Al proportion was 5 mol %, the Si proportion was 0.5 mol %, and the Fe proportion was 1 mol %.
[0101] In addition, the lithium transition metal oxide of Example 3-6 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1, and diffraction lines indicating a layered structure were confirmed. The ratio of metal elements other than Li present in the Li layer was 1.4 mol%, the half-width of the diffraction peak of the (208) plane was 0.33°, the lattice constant a was 2.873 Å, the lattice constant c was 14.20 Å, and the crystallite size s was 587 Å. This was used as the positive electrode active material of Example 3-6. Using the positive electrode active material of Example 3-6, a test cell was prepared in the same manner as in Example 1, and the self-heating start temperature was measured under the same conditions as above. In addition, a test cell was prepared using a lithium transition metal oxide that did not contain Mn and had a Ni ratio of 90.5 mol%, a Co ratio of 4.5 mol%, and an Al ratio of 5 mol% as the positive electrode active material, and the self-heating start temperature (reference value) was measured under the same conditions as above to determine the self-heating start temperature change amount of Example 3-6. The results are shown in Table 3.
[0102] <Example 3-7> Composite oxide containing Ni, Mn and Co (Ni 0.94 Mn 0.04 Co 0.02 A lithium transition metal oxide was produced in the same manner as in Reference Example 3-1, except that O2) and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, and Co to Li was 1:1.05, and the maximum temperature reached during firing was changed to 700° C. The proportions of Ni, Mn, and Co in the lithium transition metal oxide obtained above were measured, and the results were that the proportion of Ni was 94 mol %, the proportion of Mn was 4 mol %, and the proportion of Co was 2 mol %.
[0103] In addition, the lithium transition metal oxide of Example 3-7 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1, and diffraction lines indicating a layered structure were confirmed. The ratio of metal elements other than Li present in the Li layer was 2.1 mol%, the half-width of the diffraction peak of the (208) plane was 0.44°, the lattice constant a was 2.875 Å, the lattice constant c was 14.21 Å, and the crystallite size s was 607 Å. This was used as the positive electrode active material of Example 3-7. Using the positive electrode active material of Example 3-7, a test cell was prepared in the same manner as in Example 1, and the self-heating start temperature was measured under the same conditions as above. In addition, a test cell was prepared using a lithium transition metal oxide as the positive electrode active material, which was free of Mn, had a Ni ratio of 94 mol%, a Co ratio of 1.5 mol%, an Al ratio of 4.5 mol%, a ratio of metal elements other than Li present in the Li layer of 1.7 mol%, and a half-width of the diffraction peak of the (208) plane of 0.47, and the self-heating onset temperature (reference value) was measured under the same conditions as above to determine the self-heating onset temperature change of Examples 3-7. The results are shown in Table 3.
[0104] <Reference example 3-8> Composite oxide containing Ni, Mn, Co and Al (Ni 0.955 Mn 0.02 Co 0.02 Al 0.05 A lithium transition metal oxide was produced in the same manner as in Reference Example 3-1, except that O2) and LiOH were mixed so that the molar ratio of the total amount of Ni, Mn, Co, and Al to Li was 1:1.05, and the maximum firing temperature was changed to 700° C. The proportions of Ni, Mn, Co, and Al in the lithium transition metal oxide obtained above were measured, and the results were that the Ni proportion was 95.5 mol %, the Mn proportion was 2 mol %, the Co proportion was 2 mol %, and the Al proportion was 0.5 mol %.
[0105] In addition, the lithium transition metal oxide of Reference Example 3-8 was subjected to powder X-ray diffraction measurement in the same manner as in Example 1, and diffraction lines indicating a layered structure were confirmed. The ratio of metal elements other than Li present in the Li layer was 2.1 mol%, the half-width of the diffraction peak of the (208) plane was 0.42°, the lattice constant a was 2.875 Å, the lattice constant c was 14.21 Å, and the crystallite size s was 425 Å. This was used as the positive electrode active material of Reference Example 3-7. Using the positive electrode active material of Reference Example 3-7, a test cell was prepared in the same manner as in Example 1, and the self-heating start temperature was measured under the same conditions as above. In addition, a test cell was prepared using a lithium transition metal oxide that did not contain Mn and had a Ni ratio of 95.5 mol% and an Al ratio of 4.5 mol% as the positive electrode active material, and the self-heating start temperature (reference value) was measured under the same conditions as above to determine the self-heating start temperature change amount of Reference Example 3-8. The results are shown in Table 3.
[0106] [Table 3]
[0107] Table 4 shows the lattice constant a, the lattice constant c, and the crystallite size s of Examples 3-3 to 3-6 and Reference Example 3-8. [Table 4]
[0108] As can be seen from the results in Table 3, in all of Examples 3-2 to 3-7, the self-heating starting temperature of the battery was increased, and the thermal stability of the positive electrode active material was improved.
[0109] From the above results, it can be said that a positive electrode active material having a layered structure and containing Ni, Mn, and an optional element Co, wherein the ratio of Ni to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 75 mol % to 95 mol %, the ratio of Mn to the total amount of metal elements excluding Li in the lithium transition metal oxide is equal to or greater than the ratio of Co to the total amount of metal elements excluding Li in the lithium transition metal oxide, the ratio of Co to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 0 mol % to 2 mol %, the ratio of metal elements other than Li present in the Li layer of the layered structure is in the range of 1 mol % to 2.5 mol % to the total amount of metal elements excluding Li in the lithium transition metal oxide, and the lithium transition metal oxide has an X-ray diffraction pattern in which the half width n of the diffraction peak of the (208) plane is 0.30°≦n≦0.50°, can improve thermal stability.
Claims
1. a lithium transition metal oxide containing Ni, Mn and optionally Co, having a layered structure; The ratio of Ni to the total amount of metal elements excluding Li in the lithium transition metal oxide is in the range of 75 mol % to 95 mol %, a ratio of Mn to the total amount of metal elements excluding Li in the lithium transition metal oxide is greater than a ratio of Co to the total amount of metal elements excluding Li in the lithium transition metal oxide; The lithium transition metal oxide has an X-ray diffraction pattern in which the half-width n of a diffraction peak on a (208) plane satisfies the range of 0.33°≦n≦0.45°.
2. 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein a ratio of Co to a total amount of metal elements other than Li in said lithium transition metal oxide is in a range of 0 mol % to 2 mol %.
3. 3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal oxide contains Al.
4. 4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal oxide has a lattice constant a indicating the a-axis length of a crystal structure obtained from an analysis result of an X-ray diffraction pattern by X-ray diffraction, and a lattice constant c indicating the c-axis length of the crystal structure are in the ranges of 2.867 Å≦a≦2.877 Å and 14.18 Å≦c≦14.21 Å.
5. 5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal oxide has a crystallite size s in the range of 400 Å≦s≦600 Å, the crystallite size s being calculated from the half-width of a diffraction peak of a (104) plane in an X-ray diffraction pattern by Scherrer's formula.
6. A non-aqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material for non-aqueous electrolyte secondary batteries according to any one of claims 1 to 5.
Citation Information
Patent Citations
Lithium transition-metal compound oxide for positive electrode active material for lithium secondary battery, and manufacturing method thereof
JP2003017049A
Cathode active material and lithium secondary battery equipped therewith
JP2013538003A
Positive electrode active material for lithium ion secondary battery, method of producing the same, and lithium ion secondary battery
JP2016081903A
Lithium-nickel-containing composite oxide and nonaqueous electrolyte secondary battery
JP2017226576A
Positive electrode active material, and positive electrode and lithium secondary battery comprising the same
KR1020160105348A